DARI TEOLOGI PEMBANGUNAN KE TEOLOGI PERDAMAIAN - Chirzin, M. Habib (Jurnal Bestari, 1992)
Every Religion has a system of theology. It discusses many concepts of religious thought that include the existence of God. The discussion of the existence God, however, must be related to is creations. All creatures in this universe will return to Him. The nature of theology changes in accordance with the changes of the world. When the developing countries started to develop their land and people, the main topic of theology often related to the ideas of development. Recently, the theology of development was replaced by the theology of peace.